Differences in Multimodal Electroencephalogram and Clinical Correlations Between Early-Onset Alzheimer’s Disease and Frontotemporal Dementia - Lin, Nan; Gao, Jing; Mao, Chenhui; Sun, Heyang; Lu, Qiang; Cui, Liying (Frontiers in Neuroscience, 2021)
Background. Alzheimer’s disease (AD) and frontotemporal dementia (FTD) are the two main types of dementia. We investigated the electroencephalogram (EEG) difference and clinical correlation in early onset Alzheimer’s disease (EOAD), and FTD using multimodal EEG analyses. EOAD had more severe EEG abnormalities than late onset AD (LOAD). Group comparisons between EOAD and LOAD were also performed. Methods. Thirty patients diagnosed with EOAD, 9 patients with LOAD and 14 patients with FTD (<= 65y) were recruited (2008.1-2020.2), along with 24 healthy controls (<=65y, n=18; >65y, n=6). Clinical data were reviewed. Visual EEG, EEG microstate and spectral analyses were performed. Results. Compared to controls, markedly increased mean microstate duration, reduced mean occurrence and reduced global field power (GFP) peaks per second were observed in EOAD and FTD. We found increased durations of class B in EOAD and class A in FTD. EOAD had reduced occurrences in classes A, B and C, while only class C occurrence was reduced in FTD. The visual EEG results did not differ between AD and FTD. Microstate B showed correlations with activities of daily living score (r = 0.780, P = 0.008) and cerebrospinal fluid (CSF) Aβ42 (r = -0.833, P = 0.010) in EOAD. Microstate D occurrence was correlated with CSF Aβ42 level in FTD (r = 0.786, P = 0.021). Spectral analysis revealed a general slowing EEG, which may contribute to microstate dynamic loss. Power in delta was significantly higher in EOAD than FTD all over the head. In addition, EOAD had marked increased duration and decreased occurrence than late onset AD (LOAD), with no group differences in visual EEG results. Conclusions. The current study found that EOAD and FTD had different EEG changes, and microstate had association with clinical severity and CSF biomarkers. EEG Microstate is more sensitive than visual EEG, and may be useful for differentiation between AD and FTD. The observations support that EEG can be a potential biomarker for diagnosis and assessment of early onset dementias.